Warum eben Holland? Zur Anwendbarkeit theoretischer Ansätze zeitgenössischer niederländischer Gesellschaftswissenschaftler bei der Interpretation des Romans Die Geschichte meiner Frau von Milán Füst - Takács, Miklós (Acta Neerlandica, 2015)
The present study tries to re-read Milán Füst’s novel with the help of theories of three contemporary Dutch scholars. Mieke Bal’s academic bestseller, The Travelling Concepts helps us to recognize that static notions of masculinity as well as national and gender stereotypes, which are challenged by the novel, have always been changing dynamically. On the basis of Johan Goudsblom’s theories on the relationship between fire and civilization, on time regimes and on the mystery of the origin of the masculine power one can also prove that Füst’s novel keeps on playing with virtues believed to be masculine, such as the self-control and power over the women. And finally, the essays of the socio-psychologist Douwe Draaisma provide explanation for how the autobiographical memory of the narrator-protagonist determines the special narrative structure of the novel, why he is dwelling on superfluous details and why he leaves out years of his life story.